Concealing the diacritical marks and its impact on the multiplicity of meaning in the Quran, with the" Bahr al-Muhit" as an example - Alkrenawi, Fareda Jmeaan Mahmood (Journal of Arabic Language Sciences and Literature, 2024)
This study pays attention to the hiddenness of the grammatical sign, and its impact on the multiplicity of grammatical aspects and meaning, in the Holy Qur’an, based on the interpretation of Al-Bahr Al-Muhit by Abu Hayyan which is considered one of the most important exegeses that delved deeply into the linguistic aspects of the Quranic text, distinct from mere interpretation and addressing the essence of the text. The significance of meaning was elevated in Abu Hayyān's interpretation in general, and his reliance on common linguistic elements in particular.The grammatical mark in the books of grammatical thought is related to the factor theory. As it is closely related to it; The factor is the letter or verb and what is derived from it, and the verbal change is the difference in the movements that appear at the end of the speech. As for the discretionary change, it is the estimation of the movements in what does not appear in it for a purpose or an obstacle, such as impossibility or construction, the parsing of sentences, and some morphological symptoms,... and in this study we will The researcher explains this phenomenon, with some verses in the Holy Revelation, and how the absence of the grammatical mark in it contributed to making it a carrier of several grammatical aspects, by relying on the interpretation of Al-Bahr Al-Muhit by Abu Hayyan, and what was permitted among these aspects or what was rejected.
Keywords: invisibility of the grammatical sign; estimation; multiplicity of grammatical aspects; meaning; Abu Hayyan; Al-Bahr Al-Muhit; weighting; refutation